JENIS PAKAN DAN DAYA DUKUNG HABITAT RUSA SAMBAR (CERVUS UNICOLOR KERR, 1972) DI RESORT TELUK PULAI, TAMAN NASIONAL TANJUNG PUTING, KALIMANTAN TENGAH - Abdul Haris Mustari; Afroh Manshur; Burhanuddin Masy'ud (Department of Forest Resources Conservation and Ecotourism - IPB University, 2012)
The existence of sambar deer (Cervus unicolor) are increasingly threatened due to habitat loss and ilegal huntingt. One of sambar deer’s stronghold population in Kalimantan is Tanjung Puting National Park (TNTP). Population decline of sambar deer can be avoided by habitat management. This study aimed to reveal food plants that potentially eaten by the deer and productivity and carrying capacityof the deer’s habitat. This study was focused in Teluk Pulai Resort of TPNP. The study revealed that sambar deer consumed at least 53 species of plant including into 33 families. Parts of plants eaten by sambar deerconsisted leaves (31 species), leaves and stems (4 species), leaves and flowers (6 species), leaves and fruits (10 species) and fruit (2 species). The distribution patterns of sambar deer’s food plants were clumped distribution (57,38%), random (16,39%) and unknown (26,23%). Productivity of the habitat was 1.809.879,644 kg day-1 to 2.613.587,565 kg day-1, resulting an estimate of carrying capacity of 2 individuals ha-1. Keywords: Sambar deer, food plant, distribution pattern, carrying capacity